Uncoupling Aluminum Toxicity From Aluminum Signals in the STOP1 Pathway - Le Poder, Léa; Mercier, Caroline; Février, Laureline; Duong, Nathalie; David, Pascale; Pluchon, Sylvain; Nussaume, Laurent; Desnos, Thierry (Frontiers in Plant Science, 2022)
Aluminum (Al) is a major limiting factor for crop production on acidic soils, inhibiting root growth and plant development. At acidic pH (pH <5.5), Al3+ ions are the main form of Al present in the media. Al3+ ions have an increased solubility at pH <5.5 and results in plant toxicity. At higher pH, the free Al3+ fraction decreases in the media, but whether plants can detect Al at these pHs remain unknown. To cope with Al stress, STOP1 (SENSITIVE TO PROTON RHIZOTOXICITY1) transcription factor induces ALMT1 (AL-ACTIVATED MALATE TRANSPORTER1), a malate-exuding transporter as strategy to chelate the toxic ions in the rhizosphere. Here, we uncoupled Al signalisation from its toxicity using wild type (WT) and two stop1 mutants carrying the pALMT1::GUS construct with an agar powder naturally containing low amounts of phosphate, iron (Fe) and Al. We combined gene expression (RT-PCR and the pALMT1::GUS reporter), confocal microscopy (pSTOP1::GFP-STOP1 reporter), and root growth measurement to assess the effects of Al and Fe on the STOP1-ALMT1 pathway in roots. Our results show that Al triggers STOP1 signalling at concentration as little as 2μM and can be detected at pH above 6.0. We observed that at pH 5.7, 20μM AlCl3 induces ALMT1 in WT but does not inhibit root growth in stop1 Al-hypersensitive mutants. Increasing AlCl3 concentration (>50 μM) at pH 5.7 results in the inhibition of the stop1 mutants primary root. Using the GFP-STOP1 and ALMT1 reporters, we show that the Al signalisation can be uncoupled from the Al toxicity on root. Furthermore, we observe that Al strengthens the Fe-mediated primary root growth arrest of the WT, suggesting an interaction between Fe and Al on the STOP1-ALMT1 pathway.